Media and Democracy in Malaysia - Kim, Wang Lay (Javnost-The Public, 2001)
This article examines the basis for continued government control over the mass media in Malaysia, even though many of the main outlets are privately owned. The peculiar features of the Malay polity, with its official policies of assistance for Malays, as opposed to people of Chinese and Indian origin, is outlined as an essential background to understanding the mechanisms of media control. In the press, the combination of political party ownership of the main publications, and extremely stringent licensing conditions mean that alternative voices struggle to gain a hearing. In the case of broadcasting, a strong state sector is complemented by commercial companies that are owned by associates of the ruling party. The Internet has provided more problems for the government. Despite the fact that the main local ISP collaborates very closely with the government in tracking activity on the web, and the fact that there have been cases of persecution directly following from this surveillance, oppositional forces have had some online successes. Alongside the web of ownership, the government also has a battery of legal measures that it uses to control the media. Both press and broadcasting must be licensed, and this power is held by ministers who do not have to give any reason if they decide to revoke a permit. Most repressive of all is the Internal Security Act, bequeathed by the British and still in active use today. One measure of how effective these levers of control are is the performance of the media in elections, where they systematically foreground and praise the ruling party while denigrating or ignoring oppositional parties.